Species information in whistle frequency modulation patterns of common dolphins. (25th October 2021) - Oswald, Julie N.; Walmsley, Sam F.; Casey, Caroline; Fregosi, Selene; Southall, Brandon; Janik, Vincent M.
Abstract : The most flexible communication systems are those of open-ended vocal learners that can acquire new signals throughout their lifetimes. While acoustic signals carry information in general voice features that affect all of an individual's vocalizations, vocal learners can also introduce novel call types to their repertoires. Delphinids are known for using such learned call types in individual recognition, but their role in other contexts is less clear. We investigated the whistles of two closely related, sympatric common dolphin species, Delphinus delphis and Delphinus bairdii, to evaluate species differences in whistle contours. Acoustic recordings of single-species groups were obtained from the Southern California Bight. We used an unsupervised neural network to categorize whistles and compared the resulting whistle types between species. Of the whistle types recorded in more than one encounter, 169 were shared between species and 60 were species-specific (32 D. delphis types, 28 D. bairdii types). Delphinus delphis used 15 whistle types with an oscillatory frequency contour while only one such type was found in D. bairdii . Given the role of vocal learning in delphinid vocalizations, we argue that these differences in whistle production are probably culturally driven and could help facilitate species recognition between Delphinus species. This article is part of the theme issue 'Vocal learning in animals and humans'.